ON DIGITAL H-GROUPS - DEMİRALP, Sibel; HAMOUDA, Essam (Journal of Universal Mathematics, 2019)
In this paper, specific properties of digital H-spaces and digital H-groups are studied. It is shown that there is a contravariant functor from the homotopy category of the pointed digital images to the category of groups and homomorphisms. Then it is proven that a pointed digital image having the same digital homotopy type as a digital H-group is itself a digital H-group.
Keywords: Matematik; Digital image; digital homotopy; digital H-space; digital H-group; Mathematical Sciences